Phylogenetic study of genus Tupaia (scandentia : tupaiidae) using morphological and molecular analyses - Eileen, Lit. (Universiti Malaysia Sarawak (UNIMAS), 2011)
Morphometric and phylogenetic analyses were done on six species of genus Tupaia from Malaysia. Morphological study was done on T.montana, T. tana, T.minor, T.glis, T.gracilis, and T.picta. The primary objective of this study was to examine the intraspecific and interspecific relationships of the genus Tupaia using molecular and morphological analyses. The secondary objective was to validate any probable cryptic species and clarify the similar morphological characteristics among the taxa under study. The third objective was to document the taxanomic composition of small mammal in Malaysia especially the Tupaia species. a total of 24 characters of the cranial, dental and external were taken from 46 adult individuals of Tupaia.